Women's writing : text and context - Jain, Jasbir (Rawat Publications, 2014)
This volume brings together 34 essays on women's writing, presented by expert scholars from India. They focus on the validity of women's writing and trace its contribution to the construction of a female self. Marginalized as trivial, ghettoized as militant and subversive, opposed to the 'universal' and downgraded as concerned with the victim syndrome, women's writing has finally found a place for itself as voicing the experience of half of humanity. The 'text' of the title works at several levels. There is the literary text: fiction, novel, drama, theory, poetry, and autobiography. There is the socio-cultural text, which moves into the traditional context. There is then the bodily and physical awareness of participation in the making of this text as a reader. 'Contexts' again are multiple: the epistemological, patriarchal, legal, and social. The essays concern themselves with theoretical issues and historical perspectives, with spatial metaphors and discourse analysis, with cultural constructs and linguistic textures, with myth and mythologizing. Rebellion, defiance, madness, fantasy, and comedy are some of the strategies used by women writers to communicate and get their meaning across. The book is of value, not only to the young scholar and the fresh initiate, but it is also of equal significance to serious scholars of literature, history, and socio-cultural studies.